EFEK ANTIMIKROBA DARI EKSTRAK BIJI DAN DAUN MIMBA (Azadirachta indica A. Juss.) TERHADAP PERTUMBUHAN Malassezia globosa - Hastuti, Utami Sri (Jurnal Kedokteran Brawijaya, 2007)
Neem (Azadirachta indica A. Juss.) is a sort of a useful plant especially for health. Antimicrobial compounds in seed and leaf of neem especially are: azadirachtin, fenol, quinon, alkaloid, nimbin, nimbidin and gedunin. Malassezia globosa is a pathogenic yeast that cause dandruff on head skin.  This research is done on behalf to know: 1) the inhibition of neem seed extract to the growth of M. globosa in vitro;2) the difference of the effect of neem seed extract concentration to the growth inhibition of M. globosa in vitro; 3) the  inhibition of neem leaf extract to the growth of M.globosa; 4) the difference of the effect of leaf neem extract concentration to the growth inhibition of M. globosa in  vitro. Neem seed and neem leaf extract made in some sort of concentration, i.e: 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. The growth inhibition of M. globosa was measured by  measuring the inhibition zone diameter of the yeastgrowth on Sabouroud’s Dextrosa Agar.